The Role of Organizational Commitment in Mediating the Influence of Transformational Leadership on Organizational Performance - Choiril Ustadi Yudawanto; Grahita Chandrarin; Harianto Respati (Proceedings of International Conference of Graduate School on Sustainability, 2026)
This study aims to examine the role of organizational commitment in mediating the relationship between transformational leadership and organizational performance. The study subjects included officials from the Regional Apparatus Organizations (OPDs) of Banyuwangi Regency, considered representative of overall organizational performance, totaling 237 individuals. Based on calculations using the Slovin formula, 149 OPD officials served as the research sample. Data were collected through questionnaires and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. The results indicate that transformational leadership has a positive and significant influence on organizational commitment. Transformational leadership influences organizational performance. Furthermore, organizational commitment also positively influences organizational performance. Another important finding is that organizational commitment acts as a mediator in the relationship between transformational leadership and organizational performance. This means that a visionary, inspirational, and exemplary leadership style can foster employee commitment, thereby improving overall organizational performance. In practice, this study demonstrates the effectiveness of transformational leadership in fostering a work environment that supports employees’ emotional attachment to the organization. By increasing organizational commitment, the quality and sustainability of bureaucratic performance can be maintained amid dynamic changes and increasingly complex public service demands.